2016
DOI: 10.1021/acs.jproteome.6b00198
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Quantitative Lipidomics Analysis of Nonesterified Fatty Acids in Human Plasma

Abstract: We present a high-throughput, nontargeted lipidomics approach using liquid chromatography coupled to high-resolution mass spectrometry for quantitative analysis of nonesterified fatty acids. We applied this method to screen a wide range of fatty acids from medium-chain to very long-chain (8 to 24 carbon atoms) in human plasma samples. The method enables us to chromatographically separate branched-chain species from their straight-chain isomers as well as separate biologically important ω-3 and ω-6 polyunsatura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 35 publications
3
27
0
Order By: Relevance
“…Plasma C8 and C10 free fatty acid levels were measured by LC-MS according to the following procedure: Plasma samples (50 μL) were prepared as previously described ( 15 ). Briefly, proteins were precipitated by addition of 450 μL of isopropanol.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma C8 and C10 free fatty acid levels were measured by LC-MS according to the following procedure: Plasma samples (50 μL) were prepared as previously described ( 15 ). Briefly, proteins were precipitated by addition of 450 μL of isopropanol.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, Yang et al recently showed that basic pH was preferred for deprotonation of neutral compounds, while acidic compounds ionized better under acidic pH conditions . Such reports of “wrong‐way‐round” ionization have clearly shown that acidic mobile phases can also promote strong ionization in ESI − , thus confirming that the influence of surface‐ and gas‐phase processes is more significant than assumed in early studies and depends on both the pH and ionic strength of the electrosprayed solution . “Wrong‐way‐round” ionization is believed to be facilitated by the significant change in pH at the droplet surface versus bulk solution due to charge enrichment in the surface layer and also possibly to favorable formation of charged ions due to application of ESI potential, causing behavior different from that in bulk solution .…”
Section: Introductionmentioning
confidence: 95%
“…The mobile-phase additives commonly employed for lipidomics analysis in ESI − include 5-10 mM AmAc, 12,14,22,23 5-20 mM AmF, [24][25][26] 0.02-0.1% AA, 27,28 0.2% FA 12,27 and combinations of these salts and acids. 29 The use of 0.05% AmOH was shown to give a higher signal for the anionic phospholipids PG, PA, PS and PI (including their lyso forms) and the zwitterionic PE when compared to 10 mM AmAc.…”
Section: For Lipidomics Studies Such As Those Of Quehnberger Et Al 20mentioning
confidence: 99%
“…Among these, a wide range of substances (piperidine, organic acids, etc.) that can significantly enhance ESI ionization efficiency in negative ionization mode have been described [11,12,13,14,15]. The substances are characterized by diverse chemical properties (from organic acids to bases), and often, they demonstrate higher effectiveness compared with ammonium salts.…”
Section: Introductionmentioning
confidence: 99%